(untitled) (Metakognisi, 2023)
This study aims to describe the improvement of student learning outcomes in learning mathematics using audio-visual media in class XI PKBM Maritim. This study uses descriptive research methods in the form of classroom action research with research procedures including planning, implementation, observation and reflection. The results showed a significant increase. The average value obtained by students in the first cycle was 68.6 with the number of students who achieved the KKM as many as 13 students, (52%), then increased in the second cycle to 73.68 as many as 20 students, (80%) student learning outcomes increased amounted to (28%) and all students scored reaching the KKM (100%).